Tinjauan Komprehensif Teknologi Pemulihan Panas Terbuang (Waste Heat Recovery) pada Sistem Boiler untuk Peningkatan Efisiensi dan Reduksi Emisi - Dzaky Abdad, Muhammad Rafif; Rochma Fa’alih, Saika Khoolish; Nurhuda Rizkiawan, Wildan Yusril; Dwi Putra, Muhamad Fraja; Trisnoaji, Yuki (IRA Jurnal Teknik Mesin dan Aplikasinya (IRAJTMA), 2025)
This systematic literature review examines the application of Waste Heat Recovery (WHR) technologies in boiler systems to improve thermal efficiency and reduce CO₂ emissions. Using the PRISMA 2020 framework, 20 relevant studies published between 2010 and 2025 were selected through predefined eligibility and quality criteria. A thematic analysis was conducted to synthesize methodological approaches, performance outcomes, and implementation challenges across the included studies. The findings indicate that WHR integration can enhance thermal efficiency by up to 20.3%, provide fuel savings of 17.9%, and reduce CO₂ emissions by approximately 180 kg/MWh. Heat Recovery Steam Generators (HRSG) and Organic Rankine Cycle (ORC) systems demonstrate the highest performance levels, although their adoption is often constrained by higher capital costs and engineering complexity. The review also highlights gaps in policy incentives and regulatory support, which remain significant barriers to large-scale deployment. Overall, WHR technologies present a strategic pathway for improving industrial energy efficiency and advancing decarbonization efforts through a synergistic interplay of technological innovation, economic feasibility, and supportive policy frameworks.